Preparation method and application of a hydroquinone molecular imprinting regulated bismuth titanate-titanium dioxide photocatalytic material
Patent Information
- Application Number
- CN202410346901.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-26
AI Technical Summary
[0004](1)目前,Ti基与Bi基光催化材料存在以下缺点:Ti基与Bi基光催化材料应用于水处理领域均具有氧化性强、稳定性好、无二次污染等优点,但光催化材料存在受光激发后产生的光生电子(e-)与光生空穴(h+)因库伦引力作用发生复合而导致光催化效率受限问题
[0027](1)针对光催化材料存在受光激发后产生的光生电子(e-)与光生空穴(h+)因库伦引力作用发生复合而导致光催化效率受限问题,本发明所制备的特殊形貌高构效关系的材料,可以有效抑制光生电子与空穴的复合,达到形貌和光催化效果的统一。
Smart Images

Figure CN118253301B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium dioxide photocatalyst technology, specifically relating to a method for preparing and applying hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic materials. Background Technology
[0002] Currently, imprinted molecules are generally considered to participate in the formation of imprinted cavities or surface molecular imprinted layers. However, the morphology regulation role of imprinted molecules in the preparation of Ti-based photocatalysts using the sol-gel method remains unclear.
[0003] Photocatalysts can be morphologically manipulated to achieve spherical, linear, and sheet-like shapes. These morphologies can be combined to form various biomimetic structural materials, such as shell-pearl-like, chloroplast-like, and sunflower-like structures, potentially improving the structure-activity relationship. Morphologically manipulated biomimetic structures, due to their unique morphologies and high structure-activity relationships, have become a hot research direction guiding the preparation of novel catalysts. Therefore, further research into the morphological manipulation of imprinted molecules, particularly their ability to form biomimetic materials, starting from their initial participation in the formation of imprinted cavities or layers, is a worthwhile area of exploration.
[0004] (1) Currently, Ti-based and Bi-based photocatalytic materials have the following disadvantages: Both Ti-based and Bi-based photocatalytic materials have advantages such as strong oxidizing power, good stability, and no secondary pollution when applied to water treatment, but photocatalytic materials have photogenerated electrons (e) after photoexcitation. - ) and photogenerated holes (h + The problem of limited photocatalytic efficiency is caused by recombination due to Coulomb attraction.
[0005] (2) Currently, the nanoparticles of doped molecularly imprinted photocatalytic materials are prone to aggregation and it is difficult to construct morphological structures that promote the improvement of structure-activity relationship, and the activity of the synthesized materials needs to be improved.
[0006] (3) Many Ti-Bi-based materials have good photocatalytic performance. However, it is difficult to selectively control the growth point of Bi-based materials on the TiO2 surface, so it is not easy to form a high-efficiency photocatalyst with special morphology and structure. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a method for preparing and applying hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic materials.
[0008] This invention, based on selective modification and morphology control, provides a Ti-Bi-based photocatalyst with a unique structure, enabling a deeper understanding of its controllable preparation mechanism and related photocatalytic surface and interface degradation reaction mechanisms. The method provided by this invention utilizes α-Bi₂O₃ as a growth template, employs hydroquinone (HDQ) molecules as an α-Bi₂O₃ protective layer, and ultimately yields Bi₂Ti₂O₇. The photocatalyst provided by this invention offers a new pathway for the efficient and selective degradation of low-concentration, recalcitrant organic pollutants in wastewater from titanium and bismuth resources for water purification, possessing significant theoretical and environmental value.
[0009] The technical solution provided by this invention is as follows:
[0010] A method for preparing hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic materials includes the following steps:
[0011] (1) Mix tetrabutyl titanate, acid solution, first alcohol solution and hydroquinone evenly to form mixture A;
[0012] (2) Mix deionized water, second alcohol solution and bismuth salt evenly to form solution B;
[0013] (3) Add solution B dropwise to mixture A and hydrolyze until product C is obtained;
[0014] (4) After aging, product C forms a wet gel, which is then dried to obtain a dry gel.
[0015] (5) The dry gel was thoroughly ground and then calcined to obtain hydroquinone molecularly imprinted bismuth titanate-titanium dioxide (abbreviated as Bi-HDQ-TiO2) photocatalyst.
[0016] Furthermore, in step (1), the acid solution is 95% to 100% (v / v) glacial acetic acid or 95 wt% to 98 wt% sulfuric acid; the first alcohol solution is anhydrous ethanol or 90% to 95% (v / v) aqueous ethanol solution;
[0017] The amount of hydroquinone used is 1.0-2.0g, tetrabutyl titanate is 20mL, acid solution is 8-16mL, and first alcohol solution is 30-40mL.
[0018] Furthermore, in step (2), the second alcohol solution is anhydrous ethanol or a 90%–95% (v / v) aqueous ethanol solution; the bismuth salt is bismuth nitrate or bismuth chloride.
[0019] Furthermore, in step (2), the amount of deionized water is 0.5 to 3 mL, the amount of second alcohol solution is 30 to 40 mL, and the amount of bismuth salt is 3 to 7 g.
[0020] Furthermore, in step (3), solution B is added dropwise while stirring, in small amounts and multiple times.
[0021] Furthermore, in step (3), the dropping rate of solution B is 1 to 3 drops per second, and vigorous stirring is required for 2 to 3 hours after the dropping is completed.
[0022] Furthermore, in step (5), the initial calcination temperature is room temperature, and the temperature is gradually increased to a final calcination temperature of 550℃~600℃, and the calcination time is 1~3h.
[0023] Furthermore, in step (5), the calcination heating rate is 2.3℃~3℃ / min.
[0024] In a second aspect, the present invention provides a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material, which is prepared by the method described in the first aspect.
[0025] Thirdly, the present invention provides the application of the hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material described in the second aspect in the photocatalytic degradation of wastewater containing hydroquinone pollutants.
[0026] The present invention has the following advantages and beneficial effects:
[0027] (1) Regarding the photogenerated electrons (e) produced after photoexcitation of photocatalytic materials. - ) and photogenerated holes (h + The photocatalytic efficiency is limited by recombination caused by Coulomb attraction. The material with a special morphology and high structure-efficiency relationship prepared in this invention can effectively suppress the recombination of photogenerated electrons and holes, thus achieving a unity of morphology and photocatalytic effect.
[0028] (2) In view of the current situation that it is difficult to synthesize photocatalysts with special morphology by doped molecular imprinted photocatalyst materials and the activity of synthesized materials needs to be improved, the method of the present invention incorporates molecular imprinting method in the Bi doping process and can control the synthesis of photocatalysts with special morphology through process control.
[0029] (3) For many Ti-Bi based materials, it is not easy to form high-efficiency photocatalysts with special morphology structures. This invention adopts a one-step molecular imprinted sol-gel synthesis method, which has the characteristics of simple and efficient synthesis of photocatalysts with special morphology, and combines the morphology regulation effect of doping and molecular imprinting.
[0030] (4) The hydroquinone molecularly imprinted bismuth titanate-titanium dioxide (Bi-HDQ-TiO2) photocatalyst synthesized in this invention has a coral-like morphology and can achieve a degradation efficiency of 96.35% for HDQ under 30 min of ultraviolet irradiation. Attached Figure Description
[0031] Figure 1 This is a flowchart illustrating the preparation process of the photocatalyst described in this invention.
[0032] Figure 2 The SEM morphology of Bi-HDQ-TiO2 in Example 1 is as follows: (a) 20 μm, (b) 5 μm, (c) 1 μm, (d) 500 nm;
[0033] Figure 3 XRD patterns of different catalysts: (a) Bi-HDQ-TiO2, (b) TiO2, (c) Bi-TiO2; (d) N2 adsorption-desorption curves; (e) Pore size distribution of different catalysts;
[0034] Figure 4 SEM comparison: (a) Bi-TiO2; (b) Bi-HDQ-TiO2; SEM morphology of bismuth nitrate derivatives calcined at 450℃ (a mixture of Bi5O7NO3 and α-Bi2O3): (c) 1μm scale bar image, (d) 500nm scale bar image; (e) formation mechanism of the coral-like morphology of Bi-HDQ-TiO2;
[0035] Figure 5 Response surface model: (a) HDQ and Bi content, (b) calcination temperature and Bi content, (c) HDQ and calcination temperature, (d) linear regression analysis of predicted and measured values (catalyst addition amount is 1 g / L, reaction time is 30 min).
[0036] Figure 6 The design principle of the coral-like photocatalyst in Example 1 is shown in the image: coral structure (left) and coral-like Ti-Bi-based composite nano-photocatalyst structure (right).
[0037] Figure 7 The performance comparison of different catalysts in Example 1 is shown in (a), corresponding to the first-order reaction kinetics K value (b), half-life (c), and Bi-HDQ-TiO2 reuse experiment (d). Detailed Implementation
[0038] To better understand the present invention, the following embodiments are further illustrations of the present invention, but the content of the present invention is not limited thereto.
[0039] Example 1
[0040] like Figure 1 The preparation method of Bi-doped titanium dioxide molecularly imprinted catalyst with hydroquinone as the imprinted molecule is shown in the figure, and the steps are as follows:
[0041] (1) Add 20 mL of tetrabutyl titanate, 8-16 mL of 100% v / v glacial acetic acid, 30-40 mL of anhydrous ethanol and 1.0-2.0 g of hydroquinone (abbreviated as HDQ) to the same beaker and stir until well mixed to form mixture A.
[0042] (2) Add 0.5 mL of deionized water, 30-40 mL of anhydrous ethanol and 3-7 g of bismuth nitrate to another beaker and stir until well mixed to form solution B.
[0043] (3) Then, put solution B into a dropping funnel and add it dropwise to solution A under vigorous stirring. After the addition is complete, continue stirring the mixture for 2 hours to allow for complete hydrolysis. The dropping rate is 1 to 3 drops per second.
[0044] (4) After aging for 2 days, the sample becomes a wet gel. It is then placed in an oven and dried for 8 to 10 hours to obtain a dry gel.
[0045] (5) Then, the dry gel is ground thoroughly in a mortar for more than 30 minutes to achieve a uniform and fine powder state. Then, it is calcined in a muffle furnace. The initial calcination temperature is room temperature. The calcination temperature is gradually increased at a rate of 2.3℃~3℃ / min until the final temperature is stable at 550℃. After calcination for 2 hours, Bi-HDQ-TiO2 photocatalyst is obtained.
[0046] Example 2
[0047] The method is the same as in Example 1, except that Bi-HDQ-TiO2 is used as the photocatalyst and HDQ is used as the target pollutant. By adjusting the amount of HDQ (0.5, 1.5, 2.5 g), Bi(NO3)3·5H2O (3, 5, 7 g), and the calcination temperature (500℃, 550℃, 600℃) added during the preparation process, the 3D response surface plot of the degradation rate of the pollutant within 30 min was obtained as shown below. Figure 5 As shown.
[0048] like Figure 5As shown, the calculation results of the response surface model are significant within the preset interval, indicating that the fitting results are reliable. To obtain the optimal preparation conditions of Bi-HDQ-TiO2 for better degradation of HDQ wastewater, after establishing the 3D response surface model, the model can be optimized using software (Design Expert 10.0). In the software, select "Optimization," then "Numerical," and finally "Criterial" to enter the model data optimization interface. After entering the model data optimization interface, set the Bi addition amount, HDQ addition amount, and calcination temperature to "In Range," and set the 30-minute HDQ degradation rate to "Maximize," limiting the target range to 90–100%. After completing these settings, click "Solutions" to display the optimal preparation conditions suggested by the optimized software model: bismuth nitrate addition of 4.648 g, HDQ addition of 2.490 g, and calcination temperature of 546.84℃ (theoretical calculation value). At this point, the optimal operating condition can be achieved, with a degradation rate of 96.894% for HDQ wastewater after 30 minutes of photocatalytic degradation. Different response surface model optimization results can be obtained depending on different optimization requirements. The optimization results can be integers (i.e., retaining some integer conditions set in the experiment) or non-integers (i.e., the optimization results fall within the set experimental conditions). For example, in actual production, if the raw material Bi is scarce, the optimization can be set to obtain the optimal solution with the minimum Bi content.
[0049] Example 3
[0050] Performance characterization, testing, and principles:
[0051] I. Appearance
[0052] The catalyst morphology prepared in Example 1 is as follows: Figure 2 As shown.
[0053] from Figure 2 It can be seen that the dispersion of the catalyst particles is significantly improved, indicating that the addition of HDQ molecules and Bi(NO3)3·5H2O helps to suppress particle aggregation. The morphology of Bi-HDQ-TiO2 exhibits a coral-like catalyst structure of nanoparticle stacking. There are certain cracks and cavities between the stacks, reflecting a certain nucleation phenomenon. This indicates that nucleation and particle growth and accumulation around the nuclei occur during the formation of Bi-HDQ-TiO2, thus enabling the formation of this special coral-like structure.
[0054] II. Phase Structure
[0055] exist Figure 3In sample a, Bi-HDQ-TiO2 exhibits characteristics of anatase TiO2 and Bi2Ti2O7, but lacks the characteristic peaks of rutile and α-Bi2O3, indicating that the main component of both Bi-HDQ-TiO2 and Bi-TiO2 is Bi2Ti2O7-TiO2. Figure 3 In b, the XRD pattern of TiO2 exhibits characteristics of pure anatase. Figure 3 In c, the XRD pattern of Bi-TiO2 exhibits the characteristics of anatase composite bismuth titanate, which also indicates that the main component of Bi-TiO2 is Bi2Ti2O7-TiO2.
[0056] N2 adsorption-desorption experiment ( Figure 3 The results show that TiO2, Bi-HDQ-TiO2, and Bi-HDQ-TiO2 exhibit H3-type, H2-type, and H3-type adsorption hysteresis loops, respectively, within a relative pressure range of 0.4-1.0, and all conform to the Langmuir type IV curve characteristics, indicating that all four catalysts are mesoporous materials. (Pore size distribution diagram) Figure 3 e) Further verification confirmed that all four materials are mesoporous materials with pore sizes mainly distributed in the range of 20-60 nm. The BET specific surface areas of TiO2 and Bi-HDQ-TiO2 are 9.3 and 29.4 m², respectively. 2 The percentage of / g increases gradually, indicating that Bi-HDQ-TiO2 has a larger exposed area than TiO2, resulting in more surface active sites and thus higher photocatalytic activity.
[0057] II. Catalytic performance testing
[0058] 1. Testing Method
[0059] Prepare a 10 mg / L HDQ stock solution. Weigh 0.06 g of the prepared photocatalyst and add it to a quartz tube containing 60 mL of HDQ stock solution. Irradiate the test tube at a distance of approximately 10 cm using a 500 W ultraviolet mercury lamp (wavelength in the range of 200-650 nm, with a dominant wavelength of 365 nm). Take a sample every 5 minutes and place it in a 1.5 mL centrifuge tube. After 30 minutes, stop sampling. Place the sample in the centrifuge tube in a centrifuge and centrifuge at 8000 r / min for 5 minutes, repeating the centrifugation twice. Use a syringe to aspirate the supernatant after centrifugation and measure its absorbance at the characteristic wavelength of 221 nm using a spectrophotometer (UV-Vis spectrophotometer A580, Shanghai Aoyi Instrument Co., Ltd.). Convert the absorbance to concentration to calculate the change in degradation rate. Measure the HDQ degradation rate (%) using the following formula: HDQ removal rate (%) = (C0 - C) / C0 × 100%, where C0 and C are the HDQ concentrations measured before and after the reaction.
[0060] 2. Test Results
[0061] Figure 7 As shown in Figure a, Bi-HDQ-TiO2 degraded HDQ by 96.35% within 30 minutes, which is 1.53 times that of pure TiO2, indicating that the performance of the Ti-Bi composite molecularly imprinted catalyst has been significantly improved. Figure 7 Further analysis of the first-order reaction kinetics parameters of the photocatalytic degradation of HDQ using different catalysts revealed that the first-order reaction kinetic parameters for TiO2, HDQ-TiO2, Bi-TiO2, and Bi-HDQ-TiO2 were 0.0331 min. -1 0.0497min -1 0.0646min -1 0.1114min -1 The reaction efficiency of Bi-HDQ-TiO2 was increased by 3.36 times, 1.71 times, and 1.32 times compared with TiO2, HDQ-TiO2, and Bi-TiO2 (which can be abbreviated as TO, STO, and SBBTTO), respectively. Figure 7 As shown in Figure c, the half-lives for HDQ degradation by TiO2, HDQ-TiO2, Bi-TiO2, and Bi-HDQ-TiO2 were 20.97 min, 13.94 min, 10.73 min, and 6.22 min, respectively. Compared to pure TiO2, HDQ-TiO2, and Bi-TiO2, the half-life of HDQ was reduced by 14.75 min, 7.22 min, and 4.51 min when Bi-HDQ-TiO2 was selected as the photocatalyst. The improved reaction efficiency and reduced HDQ half-life indicate that the unique coral-zooxanthellae structure of Bi-HDQ-TiO2 can bring better photocatalytic performance and achieve synergistic enhancement of the structure-activity relationship.
[0062] If the substances adsorbed on the catalyst surface do not form strong chemical adsorption, simple water washing can regenerate and restore the catalyst's activity. Otherwise, acid and alkali cleaning or other regeneration methods are required. In this embodiment, the Ti-Bi-based composite photocatalyst exhibits extremely low adsorption performance and does not form stable physical or chemical adsorption with HDQ. This embodiment tests the reusability of the Bi-HDQ-TiO2 catalyst by recycling, washing, drying, and grinding, and reusing the Bi-HDQ-TiO2. Figure 7 As shown in d, Bi-HDQ-TiO2 exhibits good reusability. After four cycles, the degradation rate decreased by only 8.42%, still maintaining a degradation efficiency of 87.93%, indicating that Bi-HDQ-TiO2 has good reusability in the photocatalytic degradation of HDQ pollutants.
[0063] III. Relevant Principles
[0064] The relevant principles of this invention are as follows:
[0065] This invention utilizes a molecularly imprinted sol-gel method. In the preparation process, the method of adding solution B to solution A is altered by using a dropper for suspended drop, thus changing the bonding mechanism between bismuth nitrate and titanium dioxide sol and simulating the formation of coral-like bismuth titanate-titanium dioxide. Figure 6 As shown, TiO2 is like a coral polyp, and Bi2Ti2O7 is like a zooxanthellae. The coexistence between the two not only provides an efficient heterojunction interface, but also provides multiple electron transfer pathways, making it a highly efficient photocatalytic system.
[0066] The mechanism by which the photocatalyst achieves such high degradation efficiency is as follows: From Figure 4 It can be seen that: Figure 4 In ab, the structure of Bi-HDQ-TiO2 is more dispersed than that of Bi-TiO2, indicating an increased specific surface area and improved catalytic performance. In contrast, Bi-TiO2, lacking the addition of HDQ, allows Bi(NO3)3·5H2O to fully react with TiO2, forming a uniformly distributed Bi2Ti2O7-TiO2 microsphere structure, thus avoiding the presence of α-Bi2O3 intercalation and coral-like stacking structures.
[0067] like Figure 4 As shown in Figure cd, the product obtained by direct calcination of Bi(NO3)3·5H2O exhibits a nanosheet-like structure at 450℃. After combining Bi(NO3)3·5H2O, HDQ, and TiO2, Bi2Ti2O7-TiO2 is obtained instead of α-Bi2O3-Bi2Ti2O7-TiO2, indicating that HDQ cannot adequately protect α-Bi2O3. Interestingly, this invention yields a coral-like catalyst structure with stacked nanoparticles, which still differs significantly from the morphology of Bi-TiO2. Compared to Bi-TiO2, it is evident that the HDQ added during the preparation of Bi-HDQ-TiO2 still has a certain morphology-regulating effect, thereby delaying the conversion of α-Bi2O3 to Bi2Ti2O7. Bi2Ti2O7 gradually accumulates and grows around the α-Bi2O3 nanosheets until α-Bi2O3 is completely converted to Bi2Ti2O7, ultimately forming this coral-like catalyst. In the presence of TiO2, TiO2 can react with α-Bi2O3 to form Bi2Ti2O7, as follows:
[0068] 2TiO2 + α-Bi2O3 → Bi2Ti2O7 (1) When HDQ was added during the preparation process, the reaction underwent another slight change:
[0069] α-Bi2O3+HDQ→HDQ(α-Bi2O3)+α-Bi2O3 (4)
[0070] HDQ(α-Bi2O3)+2TiO2→Bi2Ti2O7+HDQ↑ (5)
[0071] 5TiO2+HDQ(α-Bi2O3)+α-Bi2O3→TiO2+2Bi2Ti2O7+HDQ↑=Bi-HDQ-TiO2 (6)
[0072] Therefore, under the same Ti source element content, the same Bi source element content, and the same calcination temperature and time, the catalyst with HDQ as molecular imprinted is a coral-like photocatalyst that does not contain α-Bi2O3 intercalation but uses α-Bi2O3 as a growth template.
[0073] This invention prepares Bi-doped molecularly imprinted materials based on the molecularly imprinted sol-gel method. Hydroquinone (HDQ) is used as the imprinted molecule (step 1). Bi(NO3)3·5H2O is introduced into the synthesis process of Bi-HDQ-TiO2 (steps 2 and 3). It was found that bismuth oxide is protected by HDQ within a temperature range of 0℃ to 450℃ (steps 4 and 5). As the temperature gradually rises to 550℃, after complete elution of HDQ, the surrounding TiO2 uses bismuth oxide as a nucleus and attacks it, converting it entirely into Bi2Ti2O7 (step 5). Finally, a nano-photocatalyst with a stacked coral-zooxanthellae-like structure is obtained. This unique structure allows for efficient transport of excited electrons across various surface interfaces, while simultaneously suppressing the recombination of photogenerated carriers, thereby improving photocatalytic efficiency. The synthesized coral-zooxanthellae-type catalyst achieved a degradation efficiency of 96.35% for HDQ under 30 minutes of ultraviolet irradiation, indicating that this material has broad application prospects in future environmental remediation and human health.
[0074] In the preparation method of this invention, in step (1), 20 mL of tetrabutyl titanate, 8-16 mL of glacial acetic acid, 30-40 mL of anhydrous ethanol, and 1.0-2.0 g of hydroquinone are added to the same beaker and stirred evenly to form mixture A. In step (2), 0.5 mL of deionized water, 30-40 mL of anhydrous ethanol, and 3-7 g of bismuth nitrate are added to another beaker and stirred evenly to form solution B. Step (3) introduces Bi(NO3)3·5H2O into the synthesis process of Bi-HDQ-TiO2. After the addition is complete, the mixture is stirred for 2 hours to allow for complete hydrolysis and to a certain extent protect the stability of bismuth nitrate. After aging for 2 days, the sample can become a wet gel, which keeps the catalyst in a nanoscale state. Drying it in an oven for 8 to 10 hours to obtain a dry gel ensures that the structure does not collapse due to rapid heating. HDQ further fills around the bismuth nitrate, providing a certain protective effect. Step (5) involves grinding the dry gel thoroughly in a mortar to obtain nanomaterials that are distributed as evenly as possible. Then, the gel is calcined in a muffle furnace. During this process, bismuth oxide is protected by HDQ in the temperature range of 0°C to 450°C. As the temperature gradually rises to 550°C, HDQ is completely eluted. The surrounding TiO2 uses bismuth oxide as a nucleus and attacks the bismuth oxide, causing it to be completely converted into Bi2Ti2O7 to obtain Bi-HDQ-TiO2 photocatalyst.
[0075] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the invention.
Claims
1. A method for preparing hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic materials, characterized in that, Includes the following steps: (1) Tetrabutyl titanate, acid solution, first alcohol solution and hydroquinone are mixed evenly to form mixture A; (2) Mix deionized water, the second alcohol solution and the bismuth salt evenly to form solution B; the bismuth salt is bismuth nitrate; (3) Add solution B dropwise to mixture A and hydrolyze until product C is obtained; (4) After aging, product C forms a wet gel, which is then dried to obtain a dry gel; (5) The dry gel is thoroughly ground and then calcined to obtain hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material; wherein, the initial calcination temperature is room temperature, and the temperature is gradually increased, the calcination heating rate is 2.3℃~3℃ / min, the final calcination temperature is 550℃~600℃, and the calcination time is 1~3 h; the main component of the photocatalytic material is Bi2Ti2O7-TiO2, the photocatalytic material does not contain α-Bi2O3 intercalation, but uses α-Bi2O3 as a growth template and has a coral-zooxanthellae structure of stacked growth.
2. The method for preparing a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material according to claim 1, characterized in that, In step (1), the acid solution is 95%~100% v / v glacial acetic acid or 95wt%~98wt% sulfuric acid; the first alcohol solution is anhydrous ethanol or 90%~95% v / v ethanol aqueous solution; The amount of hydroquinone used is 1.0~2.0 g, tetrabutyl titanate is 20 mL, acid solution is 8~16 mL, and first alcohol solution is 30~40 mL.
3. The method for preparing a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material according to claim 1, characterized in that, In step (2), the second alcohol solution is anhydrous ethanol or a 90%~95% v / v aqueous solution of ethanol.
4. The method for preparing a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material according to claim 1, characterized in that, In step (2), the amount of deionized water is 0.5-3 mL, the amount of the second alcohol solution is 30-40 mL, and the amount of bismuth salt is 3-7 g.
5. The method for preparing a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material according to claim 1, characterized in that, In step (3), solution B is added dropwise while stirring, in small amounts and multiple times, and after forming a suspension, it is stirred thoroughly for 2 to 3 hours.
6. The method for preparing a hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material according to claim 1, characterized in that, In step (3), the dropping rate of solution B is 1 to 3 drops per second.
7. A hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material, characterized in that: The photocatalytic material is prepared by any one of the methods described in claims 1-6. The main component of the photocatalytic material is Bi2Ti2O7-TiO2. The photocatalytic material does not contain α-Bi2O3 intercalation, but uses α-Bi2O3 as a growth template and has a coral-zooxanthellae structure with stacked growth.
8. The application of the hydroquinone molecularly imprinted bismuth titanate-titanium dioxide photocatalytic material as described in claim 7 in the photocatalytic degradation of wastewater containing hydroquinone pollutants.